Facile and low-cost fabrication of a humidity sensor using naturally available sepiolite nanofibers. (15th June 2020) - Duan, Zaihua; Jiang, Yadong; Zhao, Qiuni; Wang, Si; Yuan, Zhen; Zhang, Yajie; Liu, Bohao; Tai, Huiling
Abstract: Much effort has focussed on enhancing the humidity-sensing performances of humidity sensors, but their fabrication using facile and low-cost methods is also desirable. In this work, a humidity sensor based on a naturally available nanomaterial, sepiolite nanofibers (SNFs), was facilely fabricated without any expensive raw materials or complex processes. Characterization results show that SNFs have a natural slender nanofiber structure (diameter 20–50 nm) and abundant hydrophilic functional groups (–OH). The results of humidity-sensing tests show that the SNF humidity sensor has outstanding humidity-sensing properties (i.e. large response, good linearity and repeatability) within the relative humidity range from 10.9% to 91.5% at room temperature (25 °C). This work presents a moderate and cost-effective strategy for the fabrication of high-performance humidity sensors using the natural SNF nanomaterial.